Business Process Redesign for Intensive Care Unit in Javacare Hospital - Febrina, Imelda; Basri, Mursyid Hasan (The Indonesian Journal of Business Administration, 2014)
Abstract. Hospitals play an important role in the health care system as the main provider and server of health care. The state of health care development in Indonesia poses new challenges for hospital. In 2011, government issued a program of Universal Health Coverage (UHC) or known as Jaminan Kesehatan Nasional (JKN) to the entire people of Indonesia. The program aims to ensure that everyone is able to get health care needed.  Moreover, according to Regulation of the Ministry of Health of Indonesia Republic No.012 in 2012, due to improve hospitals’ health care service quality, hospital is required to follow the national accreditation and in an effort to improve competitiveness, hospital may follow international accreditation. To have an understanding of the hospital readiness in order to overcome the challenges, Javacare Hospital determines exploration towards factors that affect the quality of health care in hospitals. The analysis result showed that there are some weaknesses in the business process carried out by Javacare Hospital.  For that matter, Javacare Hospital needs to redesign the business process. Redesigning the business process, there are steps to be concerned: (1) methodology determination, (2) business direction definition, (3) scope and targets identification, (4) business process design, (5) implementation plan, and (6) business process implementation. Business process design is performed by using simplified Business Process Modeling Notation (BPMN). As the result, researcher creates new business process for intensive care unit in Javacare Hospital according to the requirement contain in Standar Pelayanan Minimal Rumah Sakit (SPM-RS) and JCIA Standard for Hospital. Using the new business process, it is expected that intensive care unit can support Javacare Hospital in the implementation of JKN as the government program and to obtain hospital accreditation.The implementation of new business process will caused many changes in hospital. Change management is a key component to implementation succeeds. There are four areas to address in change management: sponsorship, resistance to change, change agent skill, and organization culture and leadership. Keyword: business process reengineering, hospital accreditation, intensive care unit